Defining the Structural Stability Field of Disordered Fluorite Oxides - O’Quinn, Eric C.; Drey, Devon L.; Lang, Maik K. (Frontiers in Chemistry, 2021)
Fluorite-structured oxides constitute an important class of materials for energy technologies. Despite their high level of structural symmetry and simplicity, these materials can accommodate atomic disorder without losing crystallinity, making them indispensable for uses in environments with high temperature, changing chemical compositions, or intense radiation fields. In this contribution, we present a set of simple rules that predict whether a compound may adopt a disordered fluorite structure. This approach is closely aligned with Pauling’s rules for ionic crystal structures and Goldschmidt’s rules for ionic substitution.